The Revised METRIQ Score: A Quality Evaluation Tool for Online Educational Resources. Issue 4 (30th July 2019) - Colmers‐Gray, Isabelle N.; Krishnan, Keeth; Chan, Teresa M.; Trueger, N. Seth; Paddock, Michael; Grock, Andrew; Zaver, Fareen; Thoma, Brent
Abstract: Background: With the rapid proliferation of online medical education resources, quality evaluation is increasingly critical. The Medical Education Translational Resources: Impact and Quality (METRIQ) study evaluated the METRIQ‐8 quality assessment instrument for blogs and collected feedback to improve it. Methods: As part of the larger METRIQ study, participants rated the quality of five blog posts on clinical emergency medicine topics using the eight‐item METRIQ‐8 score. Next, participants used a 7‐point Likert scale and free‐text comments to evaluate the METRIQ‐8 score on ease of use, clarity of items, and likelihood of recommending it to others. Descriptive statistics were calculated and comments were thematically analyzed to guide the development of a revised METRIQ (rMETRIQ) score. Results: A total of 309 emergency medicine attendings, residents, and medical students completed the survey. The majority of participants felt the METRIQ‐8 score was easy to use (mean ± SD = 2.7 ± 1.1 out of 7, with 1 indicating strong agreement) and would recommend it to others (2.7 ± 1.3 out of 7, with 1 indicating strong agreement). The thematic analysis suggested clarifying ambiguous questions, shortening the 7‐point scale, specifying scoring anchors for the questions, eliminating the "unsure" option, and grouping‐related questions. This analysis guided changes that resulted in the rMETRIQ score. Conclusion: Feedback on the METRIQ‐8 score contributed to the development of the rMETRIQ score, which has improved clarity and usability. Further validity evidence on the rMETRIQ score is required.